Baby universe operators in the ETH matrix model of double-scaled SYK - Kazumi Okuyama (Journal of High Energy Physics, 2024)
Abstract We consider the baby universe operator B a $$ {\mathcal{B}}_a $$ in the double-scaled SYK (DSSYK) model, which creates a baby universe of size a. We find that B a $$ {\mathcal{B}}_a $$ is written in terms of the transfer matrix T, and vice versa. In particular, the identity operator on the chord Hilbert space is expanded as a linear combination of B a $$ {\mathcal{B}}_a $$ , which implies that the disk partition function of DSSYK is written as a linear combination of trumpets. We also find that the thermofield double state of DSSYK is generated by a pair of baby universe operators, which corresponds to a double trumpet. This can be thought of as a concrete realization of the idea of ER=EPR.